2017
DOI: 10.1149/2.0051710jes
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Reaction Mechanism of (La0.58Sr0.40)(Co0.20Fe0.80)O3-δCathode with Volatile Chromium Species at High Current Density in a Solid Oxide Fuel Cell Stack

Abstract: Anode-supported solid oxide fuel cells with different Cr protection layers on the metallic interconnect were operated in a short stack at 700 • C for 1240 h. The current density was raised sequentially from 0.5 A cm −2 during the first 240 h of operation to 0.75 A cm −2 for a further 1000 h. After operation, the (La,Sr)(Co,Fe)O 3-δ (LSCF) cathode layers were analyzed with respect to Cr interaction by both wet chemical and microstructural methods. For cells equipped with interconnects coated with a dense APS pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 47 publications
(76 reference statements)
2
30
1
Order By: Relevance
“…As stated previously, chemical analysis showed that chromium can also be found in higher amounts at the air inlet than at the air outlet. This phenomenon has been shown before: strontium chromate is more likely to form at the air inlet than at the air outlet (25). Additionally, LSCF is obviously not stable over 18 000 hours in electrolysis mode and strontium diffuses into the electrolyte as well as to the top of the cell.…”
Section: Investigation Of Layer 2 -Effects Of the Burningmentioning
confidence: 77%
“…As stated previously, chemical analysis showed that chromium can also be found in higher amounts at the air inlet than at the air outlet. This phenomenon has been shown before: strontium chromate is more likely to form at the air inlet than at the air outlet (25). Additionally, LSCF is obviously not stable over 18 000 hours in electrolysis mode and strontium diffuses into the electrolyte as well as to the top of the cell.…”
Section: Investigation Of Layer 2 -Effects Of the Burningmentioning
confidence: 77%
“…We applied this diagram to explain Cr species deposition under real stack operation conditions. More detailed information can be found in the co‐work with A. Beez …”
Section: Thermodynamic Aspects Of Cr Poisoningmentioning
confidence: 99%
“…The amount of Cr deposited on the cathode strongly depends on the Cr protection coating applied to the interconnect and the operating temperature (Beez et al, 2017). For stacks with less efficient Cr protection coatings (e.g., porous coatings applied by wet powder spraying), which were operated for up to 17.000 h, we measured a Cr content in the range of 100-200 µg cm −2 on the stack level (Menzler et al, 2011;Menzler and Batfalsky, 2012;Beez et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of Cr deposited on the cathode strongly depends on the Cr protection coating applied to the interconnect and the operating temperature (Beez et al, 2017). For stacks with less efficient Cr protection coatings (e.g., porous coatings applied by wet powder spraying), which were operated for up to 17.000 h, we measured a Cr content in the range of 100-200 µg cm −2 on the stack level (Menzler et al, 2011;Menzler and Batfalsky, 2012;Beez et al, 2017). So far a non-linear correlation between the amount of Cr deposited on an LSCF cathode and the operation time of a stack was measured (Menzler and Batfalsky, 2012) and a Cr content in the range of 200 µg cm −2 is the highest value reached for JÜLICH ASC stacks so far.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation